2005
DOI: 10.1002/cne.20652
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous activation of mouse main and accessory olfactory bulbs by odors or pheromones

Abstract: It is generally believed that the main olfactory system processes common odors and the accessory olfactory system is specifically for pheromones. The potential for these two systems to respond simultaneously to the same stimuli has not been fully explored due to methodological limitations. Here we examine this phenomenon using high-resolution functional magnetic resonance imaging (fMRI) to reveal simultaneously the responses in the main (MOB) and accessory olfactory bulbs (AOB) to odors and pheromones. Common … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
135
2
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(152 citation statements)
references
References 67 publications
14
135
2
1
Order By: Relevance
“…without direct physical contact with the olfactory source) remains controversial but some experiments reported the activation of the AOB by volatile compounds delivered in the airstream [70,118]. In addition, other indirect behavioral evidence for a role of the VNO in the detection of volatile molecules comes from the study by Trinh and Storm [109], who used transgenic mice with a nonfunctional cAMP signaling pathway in the olfactory epithelium due to a mutation in type 3 adenylyl cyclase (AC3).…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%
“…without direct physical contact with the olfactory source) remains controversial but some experiments reported the activation of the AOB by volatile compounds delivered in the airstream [70,118]. In addition, other indirect behavioral evidence for a role of the VNO in the detection of volatile molecules comes from the study by Trinh and Storm [109], who used transgenic mice with a nonfunctional cAMP signaling pathway in the olfactory epithelium due to a mutation in type 3 adenylyl cyclase (AC3).…”
Section: Functional Roles Of Both the Main And The Accessory Olfactormentioning
confidence: 99%
“…Activity mapping studies have shown that glomeruli within this area of the olfactory bulb are most responsive to urinary odors (Schaefer, Yamazaki, Osada, Restrepo, & Beauchamp, 2002;Xu et al, 2005), and that c-Fos expression in associated periglomerular cells in this part of the olfactory bulb is increased by urine exposure. For each animal, four sections at approximately Bregma 1.70mm (see Figure 1a) were selected for the anterior piriform cortex and c-Fos neurons were bilaterally counted within a 600µm x 450µm box laid over this area.…”
Section: Exposure To Estrous Urine and C-fos Immunohistochemistrymentioning
confidence: 99%
“…Although AOB is not present in humans (Meisami et al, 1998), it is an attractive region for study because of its simple structure, consisting of only three types of neurones (Mori, 1987) and its implicated functions such as information integration (Xu et al, 2005;Hendrickson et al, 2008) or memory storage (Kaba et al, 1994;Matsuoka et al, 2004;Binns and Brennan, 2005).…”
Section: Introductionmentioning
confidence: 99%